Sosialiasi Sistem Penilaian Akreditasi (SisPenA) Badan Akreditasi Nasional Pendidikan Anak Usia Dini (PAUD) dan Pendidikan Non Formal (PNF) di Kecamatan Bantan, Kabupaten Bengkalis, Propinsi Riau - Hadion Wijoyo (JPM: Jurnal Pengabdian Masyarakat, 2020)
Accreditation of Early Age Education and Non-Formal Education Unit (Dikmas) is contained in Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System. In accordance with the policies of the National Accreditation Board for Early Childhood Education (PAUD) and Non Formal Education (PNF) of the Republic of Indonesia, the submission of PAUD and PNF accreditation units since 2018 must go through the Sispena application (Accreditation Submission System) or using the Online system